2014
DOI: 10.1371/journal.pntd.0002820
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Features and Environmental Risk Factors of Severe Fever with Thrombocytopenia Syndrome, Xinyang, China

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease discovered in rural areas of Central China in 2009, caused by a novel bunyavirus, SFTS virus (SFTSV). The disease usually presents as fever, thrombocytopenia, and leukocytopenia, with case-fatality rates ranging from 2.5% to 30%. Haemaphysalis longicornis was suspected to be the most likely vector of SFTSV. By the end of 2012, the disease had expanded to 13 provinces of China. SFTS patients have been reported in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 20 publications
5
68
0
Order By: Relevance
“…SFTS cases are mainly distributed among farmers living in mountainous or hilly rural areas (19). So far, more than two-thirds of the provinces in mainland China have reported cases of SFTS.…”
Section: Discussionmentioning
confidence: 99%
“…SFTS cases are mainly distributed among farmers living in mountainous or hilly rural areas (19). So far, more than two-thirds of the provinces in mainland China have reported cases of SFTS.…”
Section: Discussionmentioning
confidence: 99%
“…One such study used a Poisson regression analysis to show that the spatial variations in the incidence of SFTS were significantly associated with shrub, forest and rain-fed cropland areas in the Xinyang region of the Henan province in China [18]. Another study conducted spatial scan statistics and multivariate model of SFTS in China using the surveillance data from 2010 to 2013, and they detected three hot spots of SFTS in China and identified independent risk factors of the distribution of SFTS [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies showed that tick-borne diseases like Lyme disease, rickettsiosis and tick-borne encephalitis have a strong association with environmental factors [25,26,27]. Considering that the majority of patients of confirmed SFTS cases lived in rural areas and were employed in agriculture [8,18], we hypothesize SFTS might be influenced by environmental factors and anthropogenic factors. Our study has two major objectives: (1) to identify the factors of SFTSV based on data from seven provinces with SFTSV cover and other provinces that had no reported cases; (2) to predict high-risk areas in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with this virus shows a case-fatality rate of ≈12% in humans ( 5 , 6 ). Severe disease progression of patients infected with SFTSV has further been associated with increased cytokine and chemokine responses ( 7 ) and increased viremias throughout the course of disease ( 6 ).…”
mentioning
confidence: 99%